Organizational wellbeing: A model of a new Apulian COVID-19 designated hospital - Vimercati, Luigi; Cannone, Enza Sabrina Silvana; Sponselli, Stefania; Caputi, Antonio; Migliore, Giovanni; Daleno, Antonio; Minicucci, Anna Maria; Milone, Gabriella; Spagnolo, Lorenzo; Pipoli, Antonella; De Maria, Luigi (Frontiers in Public Health, 2022)
Background Work environment characteristics have an important impact on organizational wellbeing in health care facilities. In the Apulia Region, a new COVID-19 hospital was planned, designated and built in a few weeks for the treatment of patients infected with SARS-CoV-2. To our knowledge, this hospital, together with “Fiera Hospital” in Milan, are two of the few buildings worldwide that have been converted into new health care facilities with intensive care center units to treat COVID-19 patients, and this is the first study assessing organizational wellbeing in a newly designated COVID-19 hospital. Aims To detect and assess the strong points, criticality, and perceptions of wellbeing/discomfort of health care workers engaged in the management of the current health emergency. Method The study was conducted on 188 health care workers, with the “Multidimensional Organizational Health Questionnaire.” Results We found an overall positive level of organizational wellbeing. The more positive dimensions were “Collaboration between colleagues,” “Organizational efficiency” and “Room Comfort.” Conflict situations in the workplace were poorly perceived. A very low rate of absenteeism from work was also observed. Conclusions Our results show the effectiveness of the organizational model adopted in the management of the COVID-19 hospital, especially in view of the work and emotional overload of the personnel called to face the epidemiological emergency on the frontline, which did not adversely affect the psychophysical conditions of the workers. The success of this model is related to the coexistence of all levels of care required during any type of health emergency in a single structure, paying particular attention to the architectural, functional, and procedural aspects of health care and to the so-called “humanization” of care.